Natak Naari Ke Man Aur Mashtishk Ka Dwand: Exploring the Dichotomy of the Mind and Brain in Female Theater Performances (Journal of Advances and Scholarly Researches in Allied Education, 2013)
^^ dkO;s’kq ukVdae~ jE;e~ ^^ dg djlaLd`rkpk;ksZa us vkSj ^^ ukVd thou dh vuqd`fr gS^^ ¼Mªkek bZt bfeV’ku vkWQykbQ½ dgdj vkaXl leh{kdksa us bl n`’;kRed lkfgR;d fo/kk vkSj thou ds laca/k dh?kfu"Brk dks n`